Strategies for Intervention and Prevention in Online Child Sexual Exploitation - Ali, Muhammad Imran (Teisė, 2024)
Online child sexual exploitation (OCSE) is a significant societal and technological problem that ought to be addressed immediately. This article broadly deals with the intricate complexity of OCSE, laying bare the identities and behaviors of online predators, the characteristics of virtual playgrounds, and the adverse consequences for victims. Virtual offenders, by taking advantage of the anonymity of internet spaces, mostly use a variety of tactics to approach vulnerable children. These tactics demand thorough assessment to work out and deliver effective interventions. Virtual environments, such as game communities and chat rooms, have become the perfect hunting grounds for predators, which accentuates the crucial need for preventive measures. Nonetheless, technology gives reason for optimism about the elimination of OCSE despite the challenges of scale and precision. This article, therefore, conducts an in-depth analysis of the issue of online child sexual exploitation and offers comprehensive interventions as a way of increasing knowledge and mobilizing action to shield children from online child sexual exploitation.